PROJECT-BASED LEARNING AS A MEANS OF INTEGRATING NATURAL SCIENCE KNOWLEDGE IN MEDICAL EDUCATION - Yusupova Nazira Ikramovna (Uzbekistan Open Conference, 2025)
The article discusses modern approaches to the implementation of project-based learning (PjBL) technology in the system of higher medical education. An analysis of foreign studies devoted to the application of project-based learning in medical universities has been conducted. The experience of implementing the project-based approach at the Federal University of Vales do Jequitinhonha and Mucuri (Brazil), the University of Sydney (Australia), the Northern State Medical University, and the Izhevsk State Medical Academy (Russia) is presented.
Keywords: project-based learning; interdisciplinary competencies; research activity; educational innovations; higher medical education